Electrical and magnetic properties of antiferromagnetic semiconductor MnSi2N4 monolayer - Chen, Dongke; Jiang, Zhengyu; Tang, Ying; Zhou, Junlei; Gu, Yuzhou; He, Jing-Jing; Yuan, Jiaren (Frontiers in Chemistry, 2022)
Two-dimensional antiferromagnetic semiconductors have triggered significant attention due to their unique physical properties and broad application in spintronic devices. Based on first-principles calculations, a novel two-dimensional (2D) antiferromagnetic material MnSi2N4 monolayer is predicted. The calculation results show that the two-dimensional MnSi2N4 prefers an antiferromagnetic ground state with a small band gap of 0.26 eV. MnSi2N4 has strong antiferromagnetic coupling which can be effectively tuned under strain. Interestingly, the MnSi2N4 monolayer exhibits half-metallic ferromagnetic properties under an external magnetic field, in which the spin-up electronic state is metallic, while the spin-down electronic state is semiconducting. Therefore, 100% spin polarization can be achieved. Two-dimensional MnSi2N4 monolayer has potential application in the field of high-density information storage and spintronic devices.